GDPR: most common breaches committed by data controllers/processors and their causes - Beguna, Jana (Riga Graduate School of Law, 2020)
The 21st century is called “digital” not for nothing. Technological revolution, development of cyberspace and emerged amount of data flows have marked the last 50 years and opened up new opportunities for humanity. In 2016, the European Union has adopted the General Data Protection Regulation and gave its member states two years for harmonization on domestic levels. Since these two years have passed and the Regulation has come into force, the Union has been facing numerous breaches on all of its territory. The nature of infringements vary, nevertheless, some kind of tendency exists. The thesis aims at identification of the most common breaches of the General Data Protection Regulation committed by data controllers and processors, and explains their causes in order to make this tendency clear.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Data protection